Diagnostics, results and nursing interventions focused on the community in the covid-19 pandemic (Research, Society and Development, 2020)
Objective: to identify nursing diagnoses according to the NANDA taxonomy, list relevant results according to the NOC, and main interventions according to the NIC, community oriented, to face the pandemic by the COVID-19. Method: qualitative study that analyzed some documents published by the Brazilian Institute of Statistics and Geography on the data from the National Sample Survey by Household, from the Ministry of Health - Coronavirus, and on the Guidelines for Diagnosis and Treatment. Results: the study chained publications of the Brazilian Institute of Geography and Statistics - National Household Sample Survey of the Ministry of Health - Coronavirus, Guidelines for Diagnosis and Treatment, to identify nursing diagnoses and list NOCs and NICs. Three diagnoses were chosen and their consequent results and interventions. Conclusion: this work contributes to the instrumentalization of nurses to assist the community, family and individual in this first moment of the pandemic.